Prospective Prediction of Juvenile Homicide/Attempted Homicide among Early-Onset Juvenile Offenders - Baglivio, Michael T. (International journal of environmental research and public health, 2017)
While homicide perpetrated by juveniles is a relatively rare occurrence, between 2010 and 2014, approximately 7%–8% of all murders involved a juvenile offender. Unfortunately, few studies have prospectively examined the predictors of homicide offending, with none examining first-time murder among a sample of adjudicated male and female youth. The current study employed data on 5908 juvenile offenders (70% male, 45% Black) first arrested at the age of 12 or younger to prospectively examine predictors of an arrest for homicide/attempted homicide by the age of 18. Among these early-onset offenders, males, Black youth, those living in households with family members with a history of mental illness, those engaging in self-mutilation, and those with elevated levels of anger/aggression (all measured by age 13) were more likely to be arrested for homicide/attempted homicide by age 18. These findings add to the scant scientific literature on the predictors of homicide, and illustrate potential avenues for intervention